Transformative Impact of Islamic Spiritual Care (ISC) Enriched with Murottal: Alleviating Anxiety and Depression among Coronary Heart Disease Patients through Pre- and Post-Intervention Analysis - Wisuda, Aris Citra (Public Health of Indonesia, 2024)
Background:Spiritual care is a vital component of comprehensive nursing, especially for patients in palliative care, such as those with coronary heart disease. While pharmacological and medical interventions remain the primary approach for heart-related conditions, the substantial success rate observed with spiritual therapy incorporating Murottal recitations highlights its significant impact on improving patients' quality of life, particularly in managing anxiety and depression. Objective:This study aimed to assess the differences in anxiety and depression scores among cardiovascular patients diagnosed with coronary heart disease before and after the application of Islamic spiritual care interventions using Murottal, in both intervention and control groups. Method:Using a quasi-experimental pretest-posttest design with a control group, the study involved a population of 156 coronary heart disease patients undergoing treatment. Simple random sampling produced a sample size of 110 patients at Muhammadiyah Hospital in Palembang, South Sumatra, Indonesia. Respondents were divided into two groups of 55 participants each. The intervention group received spiritual care through Murottal, while the control group received standard hospital therapy. Levels of anxiety and depression were measured using the Depression Anxiety Stress Scale (DASS). Results:The Wilcoxon test results for anxiety and depression variables in the intervention group showed a p-value of <0.005, indicating a significant difference in anxiety and depression scores before and after receiving the spiritual care intervention with Murottal. Conclusion:Islamic spiritual care (ISC) services incorporating Murottal recitations have the potential to reduce anxiety and depression among coronary heart disease patients at Muhammadiyah Hospital in Palembang, South Sumatra, Indonesia. Keywords: Anxiety, Coronary Heart Disease, Depression, Murottal, Spiritual Care, Patient.